Serum C-NLR score, a new inflammatory marker, predicts tumor histopathology and oncological outcomes of localized clear cell renal carcinoma after nephrectomy: A single center retrospective analysis: C-NLR score and clear cell renal carcinoma - Colakerol, Aykut; Temiz, Mustafa Zafer; Filtekin, Yigit Can; Sahin, Sergen; Yazar, Ramazan Omer; Ozsoy, Sule; Kandirali, Engin; Semercioz, Atilla; Muslumanoglu, Ahmet Yaser (Journal of Surgery and Medicine, 2023)
Background/Aim: Several blood and serum-based parameters have been described as prognostic markers of clear cell renal cell carcinoma (ccRCC). But most of these markers have inconsistent results and are not used in routine clinical practice. Therefore, novel potential predictor biomarkers are needed for the management of ccRCC patients in clinical practice. Here, we investigate the predictive value of a novel marker, serum C-NLR score, for pathological characteristics and oncological outcomes of ccRCC. Methods: A total of 162 RCC patients who underwent radical or partial nephrectomy between January 2015 and January 2021 were evaluated in a retrospective cohort study setting. The serum C-NLR score was compared according to the tumor histopathology-associated parameters. The predictive role of those parameters and C-NLR score on the oncological outcomes of ccRCC was also investigated. Results: The median serum C-NLR scores exhibited statistically significant increases in ccRCC patients with pathological necrosis, lymphovascular invasion, and variant differentiation. Among histopathological characteristics, only tumor necrosis and variant differentiation were associated with overall survival (OS) and tumor grade with metastasis-free survival (MFS) (no metastasis detected in grade 1–2 tumors) in Kaplan Meier analyses. Serum C-NLR score was also associated with OS but not MFS. In the univariate analyses, tumor necrosis, variant differentiation, and C-NLR score were associated with OS of localized RCC patients who underwent nephrectomy (HR: 0.29; 95% CI: 0.08–1.01; P=0.04, HR: 6.01; 95% CI: 1.66–21.82; P=0.006 and, HR: 1.21; 95% CI: 0.20–5.16; P=0.04). However, in the multivariate analysis, only variant differentiation and C-NLR score were associated with OS (HR: 1.43; 95% CI: 0.82–2.98; P=0.03 and HR: 1.21; 95% CI: 0.20–5.16; P=0.04). Tumor grade was directly associated with MFS because grade 1–2 tumors did not exhibit any metastasis. Conclusion: Serum C-NLR score was higher in worse histopathological entities. Moreover, it predicts the OS for patients with ccRCC as an independent factor.